MEREKONSTRUKSI PENGALAMAN DAKWAH SISWA SMA MELALUI MODEL INTEGRASI KONTROL DIRI DAN ILMU JIWA AGAMA DALAM PEMBELAJARAN PAI - Pradipta, Muhammad Aldam Shaka; Syahidin; Jenuri (Universitas Islam Negeri Alauddin Makassar, 2026)
Islamic Religious Education at the secondary level remains dominated by textual-cognitive approaches, leaving students' self-control capacity in dawah contexts undocumented. This study aims to understand how senior high school students narrate self-control experiences in everyday dawah situations, connect them to their religious values, and how reflective learning cycles facilitate the reconstruction of those experiences. An exploratory qualitative case study design was applied to one eleventh-grade class at SMAN 7 Bandung. Data were collected from 24 reflective journals, 30 impression-and-feedback responses, field notes, and a supplementary teacher interview, analyzed through abductive thematic analysis with hybrid coding. Findings reveal a consistent three-phase self-control pattern: impulse identification, religiously grounded inhibition, and empathy-oriented alternative action selection. Behavioral mechanisms and spiritual motivation appear to operate as an inseparable moment — a dimension absent from the quantitatively dominated Muslim adolescent self-regulation literature. A significant emergent finding is the spontaneous appearance of dawah nafsiyah as an autonomous arena in which students independently direct soul-purification inward. Student voices critically evaluating PAI as insufficiently practical reinforce that experiential learning design is not merely an academic agenda but a need articulated by students themselves. This study proposes an integration of the Self-Control Model, Islamic Religious Psychology, Experiential Learning Theory, and the Tajribi method as a framework with potential to facilitate authentic religious value internalization in regular PAI classrooms.